Quantificação de células T CD8+ CD38+ por citometria de fluxopara detecção de infecção/reativação de citomegalovírus em pacientes submetidos ao transplante de Células-Tronco Hematopoiéticas - Vania Abadia Soares Lino (2011)
Background: Infection/reactivation Cytomegalovirus (CMV) is a major cause of morbidity and mortality in immunocompromised hosts. It has already been observed in patients that have undergone kidney or liver transplantation, that CMV disease is accompanied by significant increase of circulating CD8+CD38+ T lymphocytes. In patients that received haematopoietic stem-cells (HSCT), there are no reports that address the study of this subpopulation in monitoring/diagnosis of CMV disease. Objectives: This study aimed to evaluate some cellular activation markers on circulating T lymphocytes (CD38 and HLA-DR), by flow cytometry, in patients undergoing HSCT and to stablilish its correlation with CMV disease. Methods: Blood samples of 15 patients undergoing HSCT were analysed by flow cytometry, using the following monoclonal antibodies: anti-CD3, anti-CD4, anti-CD8, anti-CD38, anti-HLA-DR, and the results were compared to CMV antigenemia, held by indirect immunofluorescence. Minitab for Windows was used for statistical analysis and a p-value < 0.05 was considered significant. Results: Patients with positive antigenemia did not show any significant increase in the percentuals of T CD8+cells expressing the activation markers CD38 or HLADR when compared to patients with negative antigenemia. On the contrary, all patients showed high percentuals of these cells independent of the presence of CMV disease. Conclusions: This study suggests that, in patients undergoing HSCT, the study of these lymphocyte sub-populations doesn't seem to contribute to the early identification of the CMV disease.